A Dynamic Optimization Approach for Solving Spine Kinematics While Calibrating Subject-Specific Mechanical Properties - Wang, Wei; Wang, Dongmei; Falisse, Antoine; Severijns, Pieter; Overbergh, Thomas; Moke, Lieven; Scheys, Lennart; De Groote, Friedl; Jonkers, Ilse (Annals of biomedical engineering, 2021)
This study aims to propose a new optimization framework for solving spine kinematics based on skin-mounted markers and estimate subject-specific mechanical properties of the intervertebral joints. The approach enforces dynamic consistency in the entire skeletal system over the entire time-trajectory while personalizing spinal stiffness. 3D reflective markers mounted on ten vertebrae during spine motions were measured in ten healthy volunteers. Biplanar X-rays were taken during neutral stance of the subjects wearing the markers. Calculated spine kinematics were compared to those calculated using inverse kinematics (IK) and IK with imposed generic kinematic constraints. Calculated spine kinematics compared well with standing X-rays, with average root mean square differences of the vertebral body center positions below 10.1 mm and below 3 . 38 ∘ for joint orientation angles. For flexion/extension and lateral bending, the lumbar rotation distribution patterns, as well as the ranges of rotations matched in vivo literature data. The approach outperforms state-of-art IK and IK with constraints methods. Calculated ratios reflect reduced spinal stiffness in low-resistance zone and increased stiffness in high-resistance zone. The patterns of calibrated stiffness were consistent with previously reported experimentally determined patterns. This approach will further our insight into spinal mechanics by increasing the physiological representativeness of spinal motion simulations.